Using Augmented Reality to Increase Interaction in Online Courses - Vafa, Sherry; Sappington, Kayla; Richardson, Rita Coombs- (International Journal of Educational Technology and Learning, 2018)
Augmented reality (AR) is technology that combines virtual reality with the real world in the form of live video imagery that is digitally enhanced with computer-generated graphics (Perdue, 2017). Augmented reality was used in a graduate level distance education course offered in the summer of 2017 to foster interaction. Students enrolled in the course had an opportunity to download and create augmented reality assignments to become familiar with the use of this technology as another tool to communicate and collaborate in online settings. Findings included primarily positive student attitudes regarding the use of AR in the online classroom.